Use of Plastic Wastes and Reclaimed Asphalt for Sustainable Development - Umar Hayat; Abdur Rahim; Ammad Hassan Khan; Zia Ur Rehman (The Baltic Journal of Road and Bridge Engineering)
The increased cost of virgin material, declining resources and increasing plastic wastes have turned the research momentum towards sustainable and green pavements. Reclaimed Asphalt Pavement (RAP) from the construction industry and plastic wastes disposal is the main problem for Pakistan as well as other developing countries in the face of fewer funds for the construction, repair, and rehabilitation of the extensive road network. In this research, the attempt has been made to study the use of Reclaimed Asphalt Pavement and plastic wastes to counter these issues. Virgin binder was modified with three different contents (2%, 4%, and 6%) of Polyethylene Terephthalate and three contents (20%, 30%, and 40%) of Reclaimed Asphalt Pavement. Conventional properties of the modified binder were determined by penetration and softening point. At the same time, thermal stability was checked by Thermal Gravimetric Analysis, and resistance against rutting was evaluated with the help of Dynamic Shear Rheometer. It is observed that modified binder remains stable up to a temperature of 470 °C and showed improved resistance against rutting. Marshall mix properties were determined and compared to specifications of the National Highway Authority of Pakistan. Optimum Marshall stability was observed with 4% Polyethylene Terephthalate, and 30% Reclaimed Asphalt Pavement, while flow and air voids remained in limits. As per the results, utilisation of plastic wastes in asphalt pavements enhances the performance and helps to reduce the environmental pollution and landfill problems due to Reclaimed Asphalt Pavement and plastic wastes.